Mental Health Practitioner's Guide to HIV/AIDS - Loue, Sana.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
The relationship is a circular one: people with mental illnesses are at increased risk for HIV infection, and individuals infected with HIV may experience a range of mental health problems, from anxiety and depression to conditions related to the disease or its treatment. Patients are not generally aware of this link, and clinicians may not have had the opportunity to have focused training on these intersecting issues. The Mental Health Practitioner$1 (Bs Guide to HIV/AIDS offers providers valuable, wide-ranging information regarding these especially vulnerable client populations. Each of its lucidly-written entries offers a digest of the basic facts and explains the salience of the topic in mental health contexts, whether the reader$1 (Bs interest is in understanding issues, boosting client coping and adherence, reducing care disparities, or improving quality of life. Also, each entry ends with a list of print references and web resources for further reading. An interdisciplinary array of HIV- and AIDS-related topics is included, such as: Populations at risk and risk behaviors Prevention, intervention, and coping strategies. Medical issues, including alternative healing, clinical trials, and aging with HIV. Care-related topics: access, standards, caregivers$1 (Bissues, and more. Social aspects, from stigmatization and partner violence to human rights and activism. Legal/ethical concepts, including informed consent, duty to warn, disclosure laws, and the Ryan White Act. The Mental Health Practitioner$1 (Bs Guide to HIV/AIDS brings expert, up-to-date knowledge to mental health care providers, such as psychiatrists, social workers, psychologists, and marriage and family therapists.s
Keywords: Social sciences; Public health; Social policy; Social work; Psychology, clinical; Social Sciences; Social Work; Clinical Psychology; Public Health; Social Policy